CRYSTALLOGRAPHIC STRUCTURE AND MAGNETIC PROPERTIES OF PSEUDOBROOKITE Fe2-XNiXTiO5 SYSTEM (x = 0, 0.1, 0.2, 0.3, 0.5 and 1) - Yosef Sarwanto; Wisnu Ari Adi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2018)
Crystallographic structure and magnetic properties of pseudobrookite Fe2-xNixTiO5 system (x = 0, 0.1, 0.2, 0.3, 0.5 and 1) have been performed through solid state reaction. Pseudobrookite Fe2-xNixTiO5 system was synthesized by mixing of Fe2O3, NiO, and TiO2 with stoichiometry composition using wet mill. The mixture was milled for 5 hours and sintered in the electric chamber furnace at 1000 oC in the air at atmosphere pressure for 5 hours. The refinement against of X-ray diffraction data shows that the sampless with composition of (x = 0) and (x = 0.1) have a single phase with Fe2TiO5 structure. However the samples with composition of (x > 0.1) consist of multiple phases, namely Fe2-xNixTiO5, FeTiO3, Fe2NiO4 and NiO. Particle morphologies of the composition x = 0 and x = 0.1 are homogenous and uniform on the sample surface with a polygonal particle shape and particle size varies. At room temperature, the sample with x=0 is paramagnetic and that with x=0.1 is ferromagnetic. Magnetic phase transformation of this study is the caused by the present of Ni substituted Fe in the system. Thus substitution Ni into Fe on the system pseudobrookite Fe2TiO5 only capable of 0.1 at.% without changing the crystal structure of the material. It means that there is an interaction between the magnetic spin Fe3+ on the 3d5 configurations and Ni2+ on the 3d3 configurations through the mechanism of double exchange. Double exchange mechanism is a magnetic type of exchange that appears between the ions Fe3+ and Ni2+ adjacent in different oxidation states.